2009
DOI: 10.3844/ajeas.2009.96.104
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of Infilled Brick Walls on Behavior of Eccentrically Braced Frames Using Explicit Finite Elements Method

Abstract: Problem statement: Eccentrically Braced Frames (EBFs) are usually infilled by masonry walls, but in common design, the stiffness and lateral resistance of these walls is ignored. Considering the results of carried out tests and studies, it seems that infilled masonry walls have a significant influence on the stiffness and the strength of EBFs. Since experimental test of total frame with infilled brick wall is a very expensive and time consuming process, proper numerical models which can precisely simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…When proceeding to the analysis of capacity of the different components of the structure, a time function is needed to express the nonlinear behavior for elements as well as for materials [38][39][40][41][42][43]. Generally, the direct numerical integration of the dynamic equilibrium is the main approach to solve the dynamic response of structural systems at a discrete point with provided time [44][45][46][47][48][49][50]. The accelerograms used in this investigation are the horizontal components of the Imperial Valley-Holtville Post Office and Imperial Valley-EL Centro (Figure 10).…”
Section: Nonlinear Time History Analyses Resultsmentioning
confidence: 99%
“…When proceeding to the analysis of capacity of the different components of the structure, a time function is needed to express the nonlinear behavior for elements as well as for materials [38][39][40][41][42][43]. Generally, the direct numerical integration of the dynamic equilibrium is the main approach to solve the dynamic response of structural systems at a discrete point with provided time [44][45][46][47][48][49][50]. The accelerograms used in this investigation are the horizontal components of the Imperial Valley-Holtville Post Office and Imperial Valley-EL Centro (Figure 10).…”
Section: Nonlinear Time History Analyses Resultsmentioning
confidence: 99%
“…The effect of brick infill walls on the seismic performance of eccentrically braced frames was studied by Daryan et al (2009). By using an explicit finite element method, they demonstrated that the presence of masonry infill can increase the elastic range of the forcedisplacement behaviour, while the plastic deformation capacity of the frame will be deteriorated due to fragility of the masonry wall.…”
Section: Introductionmentioning
confidence: 99%
“…By using an explicit finite element method, they demonstrated that the presence of masonry infill can increase the elastic range of the forcedisplacement behaviour, while the plastic deformation capacity of the frame will be deteriorated due to fragility of the masonry wall. However, the results of Daryan et al (2009) study were based on the superposition of two distinct experimental tests on a CBF and a masonry infill wall and, therefore, could not capture the actual frame-infill interaction. In a more recent study, Ahmady Jazany et al (2013) conducted a series of experimental tests to investigate the seismic performance of half-scale CBFs with masonry infill.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain acceptable results, the effect of masonry infill should be considered in the calculation of the compressive capacity of the brace elements. Daryan et al [26] investigated the effect of infill brick walls on the seismic behaviour of eccentrically braced frames using an explicit finite element method. This study showed that, in general, the presence of masonry wall increases the yield strength and the elastic range of the forcedisplacement curves.…”
mentioning
confidence: 99%